2018
DOI: 10.14419/ijet.v7i2.13.11629
|View full text |Cite
|
Sign up to set email alerts
|

Development of the mathematical model for the process of oil raw materials pressing

Abstract: The mathematical model for the process of oily raw materials pressing with single-screw oil press has been developed, which makes it possible to calculate the main design parameters of an oil press for extracting oil from oil crop seeds. This model of pressing describes the process of moving meal in the pressure zone and expression of oil in the pressing cage of the screw press, taking into account the following assumptions: porous skeleton and oil have the same density, they have no chemical interaction, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In the works of Vasylenko S. V., Kopylov M. V., Kairbaeva A. E. it was found that the percentage of shelling for squeezing oil from melon seeds is an important indicator, so when the seeds were peeled and clean from the husk, the oil yield was low, the machine strained during the extraction, with a percentage of 70/30 seeds and husks, the machine easily pressed the oil and the yield was high [2].…”
Section: Suggested Solution To the Problemmentioning
confidence: 99%
“…In the works of Vasylenko S. V., Kopylov M. V., Kairbaeva A. E. it was found that the percentage of shelling for squeezing oil from melon seeds is an important indicator, so when the seeds were peeled and clean from the husk, the oil yield was low, the machine strained during the extraction, with a percentage of 70/30 seeds and husks, the machine easily pressed the oil and the yield was high [2].…”
Section: Suggested Solution To the Problemmentioning
confidence: 99%
“…The inhibitory effect of the fermented water-honey extract of the St. John's wort grass on spore-forming bacteria Bacillus subtilis and Bacillus mesentericus was determined. A positive influence of the extract on viability of yeast cells has been established as the number of non-viable cells decreases due to a high content of easily assimilable carbohydrates, organic acids, water-soluble mineral substances and vitamins [1][2][3][4][5][6][7][8][9]. The effect of the new phytonutrient on the biotechnological and rheological properties of unbaked dough was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Modern food production reached a new step of its development when the food program shall satisfy not only the needs of the population for certain food products, but also ensure their basic nutrient balance. One of such products is salad oil [7,8,21].…”
Section: Introductionmentioning
confidence: 99%